Historians As Enablers? Historiography, Imperialism, and the Legitimization of Russian Aggression - Zayarnyuk, Andriy (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2022)
This essay raises the issue of historians’ responsibility to the communities that they study. While some purported version of history has been central to the Kremlin’s justifications for Russia’s aggression against Ukraine, the region’s historians have failed to make a stand against this misuse of history. Moreover, in many instances they endorsed and disseminated the Kremlin’s narratives about Ukraine’s past and present. Aiming to explain the anti-Ukrainian biases that have become well entrenched in both Western academia and Western public opinion, this essay examines the regional subfield of area studies, to which Ukrainian studies are usually relegated, as well as the expectations and agenda of the Western-educated public. I argue that the subfield is dominated by Russian studies and frequently uncritically adopts the positions, concepts, and explanations of Russia’s imperialist ideologists. At the same time, Western public opinion, while opening up to the historical injustices committed by Western empires, still sees the world through retrograde imperial lenses. The essay also discusses in detail what happens when researchers shaped by both these trends write Ukrainian history. Looking for ways forward, I suggest rethinking the issue of intellectual responsibility and “de-imperialization” of Ukraine’s Western historiography.